Diagnóstico del nivel de comocimiento para la preservación del medio ambiente de los niños y niñas de sexto y séptimo año de educación General básica de la escuela Rumiñahui de la parroquia Loma de Franco del cantón Pasaje durante el año lectivo 2012-2013 - Domauri Tinoco, Carlos Arístides (2013)
Basically, the primary objective of the realization of this thesis is to determine the level of knowledge for the preservation of the environment of the children of the sixth and seventh year of basic general education of the Rumiñahui school of the Loma parish. Franc of Canton Pasaje The proposal raised to this research is the construction of a community nursery in the school.